2006
DOI: 10.1002/cncr.21776
|View full text |Cite
|
Sign up to set email alerts
|

Chemoimmunotherapy with hyper‐CVAD plus rituximab for the treatment of adult Burkitt and Burkitt‐type lymphoma or acute lymphoblastic leukemia

Abstract: Invasive fungal disease (IFD) is a significant cause of morbidity and mortality in patients undergoing treatment for acute leukemia (AL). Antifungal prophylactic strategies are associated with significant toxicities and cost. We performed a retrospective study of the incidence and risk factors for IFD among patients newly diagnosed with and treated for AL between January 1, 2004 and July 1, 2006. Patient follow up concluded January 1, 2007. Among 231 patients with newly diagnosed AL, 31 (13.4%) developed IFD b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
381
3
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 493 publications
(406 citation statements)
references
References 57 publications
14
381
3
8
Order By: Relevance
“…Few phase II studies exist for Burkitt's lymphoma: results regarding response and relapse seems good but it is difficult to know the improvement secondary to rituximab use (Thomas et al, 2006). In post-transplant lymphoproliferative disease several phase II have shown a good activity with rituximab alone or in combination with chemotherapy (Milpied et al, 2000;Blaes et al, 2005;Jain et al, 2005).…”
Section: Other Lymphomasmentioning
confidence: 99%
“…Few phase II studies exist for Burkitt's lymphoma: results regarding response and relapse seems good but it is difficult to know the improvement secondary to rituximab use (Thomas et al, 2006). In post-transplant lymphoproliferative disease several phase II have shown a good activity with rituximab alone or in combination with chemotherapy (Milpied et al, 2000;Blaes et al, 2005;Jain et al, 2005).…”
Section: Other Lymphomasmentioning
confidence: 99%
“…Since B-ALL shows CD20 expression in > 80% of the cases treatment was further refined by integration of anti-CD20 before each chemotherapy cycle with very promising results of 70-80% OS in preliminary analyses. 36,37 Age-adapted treatment Subgroup-adapted therapies also have to be defined for patients at both ends of the age spectrum of adult ALL: elderly 1 and adolescent 2 patients.…”
Section: Subgroup-adjusted Treatmentmentioning
confidence: 99%
“…However, the authors observed that patients older than 60 years clearly had an inferior outcome, with a survival rate of only 17% [9]. The addition of Rituximab and the improvement in supportive care measures possibly contributed to the achievement of similar outcomes in older and younger adults [10].In 1997, we reported a monocentric experience of 21 patients (8 adults and 13 children) treated with the intensive short-term pediatric-derived chemotherapy regimen POG 8617 [11], demonstrating that the outcome in adults was not significantly different than in children [12]. Fourteen years after our original report, we present here the longterm results of the same chemotherapy regimen employed in a multicenter experience recruiting a larger cohort of 71 consecutive BL patients.…”
mentioning
confidence: 99%